Telehealth clinical learning: Understanding pre-clerkship medical student experiences - Anand, Meera; Wood, Sarah (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Background: With the onset of the COVID-19 pandemic, a reliance upon telehealth patient visits emerged. Many medical schools use early clinical experiences in the pre-clerkship years to provide opportunities to practice evolving clinical skills and broaden classroom learning. However, little is known about the value of telehealth visits during the pre-clerkship years. Therefore, the purpose of the current study was to determine what student learning experiences were with telehealth patient encounters during early clinical experiences.Methods: In this qualitative study, we used a descriptive phenomenological approach. We interviewed medical students using Zoom to gather their lived experiences. We grouped key findings into themes.Results: Seventeen medical students participated in the study. Key challenges included the loss of body language and visual cues leading to challenges with rapport building, the inability to perform physical examinations, and less involvement and independent practice of skills. However, positive aspects include good opportunities for history taking and benefits to note-taking. Mentorship with preceptors remained either positive or similar to in-person experiences.Conclusion: Since telehealth remains an important part of healthcare, it is crucial to train learners in telehealth clinical environments alongside standard in-person environments. However, while both challenges and benefits exist with telehealth clinical visits for junior learners, active learning processes, the use of video augmentation and robust faculty development strategies remain important to increase the educational value of these visits.